2016
DOI: 10.1681/asn.2016030349
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial NADP+-Dependent Isocitrate Dehydrogenase Deficiency Exacerbates Mitochondrial and Cell Damage after Kidney Ischemia-Reperfusion Injury

Abstract: Mitochondrial NADP-dependent isocitrate dehydrogenase (IDH2) catalyzes the oxidative decarboxylation of isocitrate to -ketoglutarate, synthesizing NADPH, which is essential for mitochondrial redox balance. Ischemia-reperfusion (I/R) is one of most common causes of AKI. I/R disrupts the mitochondrial redox balance, resulting in oxidative damage to mitochondria and cells. Here, we investigated the role of IDH2 in I/R-induced AKI. I/R injury in mice led to the inactivation of IDH2 in kidney tubule cells. gene del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 43 publications
1
43
1
Order By: Relevance
“…We also found that both IPC and Idh2 delivery increase states 1-3 respiratory capacity. This result stands in contrast to that of the report by Han et al, 59 in which IPC decreased IDH2 protein levels; however, our immune blots were performed on protein lysates made from kidney cortex, whereas Han et al 59 used whole-kidney lysates. Their work concluded that downregulation of IDH2 expression resulted in increased injury after AKI.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…We also found that both IPC and Idh2 delivery increase states 1-3 respiratory capacity. This result stands in contrast to that of the report by Han et al, 59 in which IPC decreased IDH2 protein levels; however, our immune blots were performed on protein lysates made from kidney cortex, whereas Han et al 59 used whole-kidney lysates. Their work concluded that downregulation of IDH2 expression resulted in increased injury after AKI.…”
Section: Discussioncontrasting
confidence: 81%
“…Their work concluded that downregulation of IDH2 expression resulted in increased injury after AKI. 59 Taken together, Idh2 delivery mimics IPC, particularly in the ability to confer protection against subsequent ischemic injury. Because it has been difficult to reproduce the protective effect of IPC in the clinical setting, it is possible that timely gene delivery offers an alternative method to prevent ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence demonstrated that ROS generation and mitochondrial membrane depolarization may lead to DNA damage and apoptosis [30, 31]. Recent studies indicated that an excess generation of mitochondrial ROS played an important role in the pathogenesis of AKI [32, 33]. The damaged mitochondria are first marked by a change of mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Excess generation of mitochondrial ROS has been found in AKI and has been considered to play an important role in the pathogenesis of AKI (20,21). Mitochondrial damage is recognized as a leading cause to many acute renal diseases (22).…”
Section: Discussionmentioning
confidence: 99%